Push–pull configuration of high-power MOSFETs for generation of nanosecond pulses for electropermeabilization of cells. Issue 7 (27th May 2019) - Davies, I. W.; Merla, C.; Casciati, A.; Tanori, M.; Zambotti, A.; Mancuso, M.; Bishop, J.; White, M.; Palego, C.; Hancock, C. P.
Abstract: A power MOSFET-based push–pull configuration nanosecond-pulse generator has been designed, constructed, and characterized to permeabilize cells for biological and medical applications. The generator can deliver pulses with durations ranging from 80 ns up to 1 µ s and pulse amplitudes up to 1.4 kV. The unit has been tested for in vitro experiments on a medulloblastoma cell line. Following the exposure of cells to 100, 200, and 300 ns electric field pulses, permeabilization tests were carried out, and viability tests were conducted to verify the performance of the generator. The maximum temperature rise of the biological load was also calculated based on Joule heating energy conservation and experimental validation. Our results indicate that the developed device has good capabilities to achieve well-controlled electro-manipulation in vitro.